Analysis of the Influence of Training and Education on the Development of MSMEs in the Community of Kwala Serapuh Langkat Village Moderated by Motivation Variables - ,, Suwarno; Andika, Rindi; Arifin, Daud; Lumbangaol, Nia Deniati (Universitas Negeri Medan, 2024)
This study aims to analyze the Influence of Training and Education on the Development of MSMEs in the Community of Kwala Serapuh Langkat Village Moderated by Motivation Variables. This study uses a quantitative method with a survey approach. The research population is all MSMEs in Kwala Serapuh Langkat village, which is as many as 120 MSMEs. The research sample is 70 MSMEs selected by the purposive sampling method. The research data was collected through questionnaires. Data analysis using SEMPLS. The government and related parties need to improve training and education programs for MSME actors. MSMEs need to increase awareness of the importance of training and education for their business development. In addition, training and education can also increase the motivation of MSME managers to develop their businesses. The results of this study directly show that Motivation does not have a significant positive influence on the development of Community MSMEs. Training has a significant positive influence on the development of Community MSMEs. Training does not have a significant positive influence on the development of Community MSMEs. Education has a significant positive influence on Community Motivation. Education has a significant positive influence on the development of community MSMEs. Meanwhile, indirectly, the training does not have a significant positive influence on the Development of Community MSMEs Moderated by Motivational Variables. Education does not have a significant positive influence on the Development of Community MSMEs Moderated by Motivation Variables